The Impact of Perceived Organizational Support and Work Environment on Employee Engagement and Job Satisfaction in Telecommunications Companies in Bandung - Amelia Trisavinaningdiah; Siska Mayratih; Isrok Isrok; Ilma Darojat; Muhammad Abdul Rosid (Westscience Press, 2026)
This study aims to examine the impact of perceived organizational support and work environment on employee engagement and job satisfaction in telecommunications companies in Bandung. A quantitative research design was applied using a survey method involving 70 employees selected through purposive sampling. Data were collected using a structured questionnaire measured with a five-point Likert scale and analyzed using SPSS version 25. The analytical techniques included descriptive statistics, validity and reliability tests, classical assumption tests, and multiple regression analysis. The results indicate that perceived organizational support and work environment have positive and significant effects on employee engagement. Furthermore, perceived organizational support, work environment, and employee engagement significantly influence job satisfaction, with employee engagement showing the strongest effect. The findings highlight that supportive organizational practices and a conducive work environment play an important role in fostering employees’ psychological attachment and satisfaction levels. This study contributes to the human resource management literature by providing empirical evidence from the telecommunications sector and offers practical implications for organizations to enhance employee engagement and job satisfaction through supportive policies and workplace improvements.